2015
DOI: 10.3167/sa.2015.590103
|View full text |Cite
|
Sign up to set email alerts
|

Living an Uncertain Future: Temporality, Uncertainty, and Well-Being among Iraqi Refugees in Egypt

Abstract: While displacement has always involved the refiguring of space, scholars of forced migration have recently begun to consider how temporality might be crucial to an understanding of displacement. In this article, I consider the interplay of temporal and spatial uncertainty in the experience of exile for Iraqi refugees in metropolitan Cairo. By examining how Iraqis understand displacement as uncertain and how this uncertainty is a cause of significant distress, I show that an attunement to temporality can help u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 17 publications
2
60
0
Order By: Relevance
“…The powerlessness and uncertainty they experienced concerning the asylum decision was often identified as the main cause of their current distress. Studies have shown that asylum processes often generate uncertainty that has negative implications for mental health (Brekke, 2010;El-Shaarawi, 2015). A study of asylum seekers in Australia showed that psychological wellbeing is dependent on the certainty of a predictable future, documenting a substantial decrease in symptoms of PTSD, anxiety, and depression in the four months following the granting of refugee status to asylum seekers (Silove et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The powerlessness and uncertainty they experienced concerning the asylum decision was often identified as the main cause of their current distress. Studies have shown that asylum processes often generate uncertainty that has negative implications for mental health (Brekke, 2010;El-Shaarawi, 2015). A study of asylum seekers in Australia showed that psychological wellbeing is dependent on the certainty of a predictable future, documenting a substantial decrease in symptoms of PTSD, anxiety, and depression in the four months following the granting of refugee status to asylum seekers (Silove et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies among refugee populations in camps or in transit concerned populations in a transit situation for years outside Europe (Akinyemi et al, 2016;El-Shaarawi, 2015;Hoffman, 2011), or mainly used epidemiological surveys as methods (Bastin et al, 2013;Crepet et al, 2017). The present study responds to the call made by Kienzler (2008) and others for mixedmethods studies of refugee mental health (Weine et al, 2014).…”
Section: Refugee Mental Health and Social Sufferingmentioning
confidence: 99%
“…“Protracted uncertainty” (Horst & Grabska, , p. 1) and prolonged waiting affect refugees’ health and well‐being. Al‐Shaarawi's (, p. 49) study of Iraqis in Cairo highlights that the stresses caused by “Instability, related to the difficult conditions which disrupted refugees’ imagined life trajectories and made the future difficult to conceptualize, led to tiredness, worry, sadness and other psychological and cognitive/emotional problems.” Similarly, Biehl () shows how living in Turkish cities for prolonged periods of time causes psychological distress for refugees.…”
Section: Protracted Uncertainty and Trauma Along The Refugee Resettlementioning
confidence: 99%
“…Here, life was not merely “on hold” but disappeared from view. Sarah's narrative brings into relief “the interplay of temporal and spatial uncertainty” (El‐Shaarawi , 38). That is, if asylum seekers were challenged to emplot their lives—to provide temporal coherence—in an effort to render lived experiences meaningful, they also simultaneously struggled to emplace themselves and bring meaning to the physical space they occupied.…”
Section: Lived Consequences Of “Existential Limbo”mentioning
confidence: 99%